(untitled) (Research, Society and Development, 2023)
Objective: To analyze hospitalizations and deaths due to acute myocardial infarction (AMI) in the state of Pará between 2015 and 2021. Methods: The records of hospitalizations and deaths were analyzed due to acute myocardial infarction in the state Between 2015 and 2021, contained in the Datasus database. Microsoft Office Excel 2016 and Bioestat® 5.4 software was used, with G and Qui-square tests for univariate and bivariate comparisons. Results: 14.439 hospitalizations were found and 19.196 deaths due to AMI. There was progressive increase in the number of hospitalizations and deaths over the years, with statistically significant predominance in the number of men, in hospitalizations and deaths, with the variables always bigger than 60%. There was a predominance of brown individuals, with low education and elderly. There was no significant difference about hospitalizations in different age groups, but there was in the relationship of deaths from 70 years. Conclusion: The epidemiological profile of patients is from men, brown, between 50 and 70 years with low level of education, with the increase in the number of deaths and hospitalizations in the period.